2000
DOI: 10.1002/1097-4628(20001213)78:12<2089::aid-app50>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic crosslinking on impact strength and other mechanical properties of polypropylene/ethylene-propylene-diene rubber blends

Abstract: The deformation and fracture behavior of several dynamic vulcanizate blends of isotactic polypropylene with ethylene‐propylene‐diene rubber (EPDM) was examined and compared with those of uncrosslinked blends of PP/EPDM. These blends were prepared by melt mixing in an internal mixer at 190°C in a composition range of 10–40 wt % EPDM rubber. The variation in yield stress, the strength of fibrils of the craze, and the number density of the EPDM rubber domains (morphology fixation) that are dominant factors for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…Several authors have reported an increase in the crystallization temperature after (reactive) compatibilization and/or dynamic vulcanization of polymer blends consisting of a semi‐crystalline thermoplastic matrix and a dispersed amorphous phase 3–10. The results presented here indicate that the formation of graft copolymers on the interface of the dispersed amorphous phase and the matrix is the major reason for the increased crystallization temperature.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Several authors have reported an increase in the crystallization temperature after (reactive) compatibilization and/or dynamic vulcanization of polymer blends consisting of a semi‐crystalline thermoplastic matrix and a dispersed amorphous phase 3–10. The results presented here indicate that the formation of graft copolymers on the interface of the dispersed amorphous phase and the matrix is the major reason for the increased crystallization temperature.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, an increase in the crystallization temperature ( T c ) from 115 °C before vulcanization up to 120 °C after vulcanization was reported 5. The formation of graft copolymers during dynamic vulcanization and an increase in the nucleating efficiency of the crosslinked rubber particles was also reported by Jain et al6 and López‐Manchado et al7 for PP/EPDM blends and by Huang et al8 for nylon/EPDM blends compatibilized with an anhydride‐grafted EPDM copolymer. Several studies on blends of poly(ε‐caprolactone) (PCL) with epoxy resins prepared via reaction‐induced phase separation (RIPS) showed a significant nucleating effect of the dispersed, amorphous epoxy phase on the PCL matrix 9–11.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This behavior can be explained by the resulting morphology and elastomeric nature of EPR. On the P 70 V 30 and P 50 V 50 blends, the existence of very small EPR domains, below 0.1 µm, highly dispersed in a continuous thermoplastic phase and with smaller interparticle distances, can induce a predominantly shear yielding mechanism of failure, rather than crazing, enhancing the matrix toughness . This mechanism can be verified by the existence of a homogeneous fracture surface on a P 70 V 30 blend specimen after the tensile test (Figure ).…”
Section: Resultsmentioning
confidence: 81%
“…In past several decades, many methods have been taken to modify the toughness of PP 5–7. Blending with elastomer is one of the effective methods to toughen PP, but at sacrifice of the strength of PP 6, 8–11. To reach a perfect balance of toughness and strength, the ternary polymer blends of PP/elastomer/nano‐particles were developed.…”
Section: Introductionmentioning
confidence: 99%